PENYUSUNAN RENCANA STRATEGIS SISTEM INDORMASI DAN TEKNOLOGI INFORMASI (SI/TI) ORGANISASI BISNIS STKIP MUHAMMADIYAH KOTABUMI MENGGUNAKAN WARD PEPPARD - Sigit Gunanto; Nisar - (Jurnal Informatika, 2019)
Information systems contribute to improving the quality of education services, operational efficiency and organizational business support. The use of information systems and information technology in a variety of teaching and learning process activities in an educational institution is not something that is complementary and additional, but a need in improving the process and the results of educational implementation of universities, therefore it is necessary to manage the information by building a system Information (SI) and supported by good and planned Information Technology (IT) to become a new strength for institutions in maintaining and increasing competitiveness. The Ward and Peppard method is a widely used model for preparing a strategic planning of an information system in an organization. With this method, various factors affecting both internal and external organizations are analyzed in such a way as to derive a new strategy. Research conducted in STKIP Muhammadiyah Kotabumi, data collection is done by doing interviews, observation and review documents. The results of this study is a strategic plan that can be poured in a portfolio that can be used as reference information system planning in STKIP Muhammadiyah Kotabumi. Keywords: Analysis of SI / IT, Ward and Peppard Method, and Strategic Planning STKIP Muhammadiyah Kotabumi.